2006
DOI: 10.5194/acp-6-3231-2006
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation in sulfuric acid/organic aerosols: implications for cirrus cloud formation

Abstract: Abstract.Using an aerosol flow tube apparatus, we have studied the effects of aliphatic aldehydes (C 3 to C 10 ) and ketones (C 3 and C 9 ) on ice nucleation in sulfuric acid aerosols. Mixed aerosols were prepared by combining an organic vapor flow with a flow of sulfuric acid aerosols over a small mixing time (∼60 s) at room temperature. No acid-catalyzed reactions were observed under these conditions, and physical uptake was responsible for the organic content of the sulfuric acid aerosols. In these experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In the case of oxalic acid the crystallization of the oxalic acid hydrate within the aqueous solution is assumed to result in organic crystals, which act as immersion mode freezing ice nuclei. Further interesting results with respect to the influence of organics on ice formation were recently published by Beaver et al (2006), who studied the effects of carbonyl compounds on the ice nucleation of sulfuric acid in the laboratory and observed that the physical properties of the organic compounds (primarily the solubility and melting point) play a dominant role in determining the inferred mode of nucleation (homogeneous or heterogeneous) and the specific freezing temperatures. Highly soluble, low-melting point organics caused a decrease in aerosol ice nucleation temperatures when compared with aqueous sulfuric acid aerosolin agreement with the homogeneous freezing experiments mentioned above.…”
Section: Ice Nucleationmentioning
confidence: 94%
“…In the case of oxalic acid the crystallization of the oxalic acid hydrate within the aqueous solution is assumed to result in organic crystals, which act as immersion mode freezing ice nuclei. Further interesting results with respect to the influence of organics on ice formation were recently published by Beaver et al (2006), who studied the effects of carbonyl compounds on the ice nucleation of sulfuric acid in the laboratory and observed that the physical properties of the organic compounds (primarily the solubility and melting point) play a dominant role in determining the inferred mode of nucleation (homogeneous or heterogeneous) and the specific freezing temperatures. Highly soluble, low-melting point organics caused a decrease in aerosol ice nucleation temperatures when compared with aqueous sulfuric acid aerosolin agreement with the homogeneous freezing experiments mentioned above.…”
Section: Ice Nucleationmentioning
confidence: 94%
“…While the homogeneous freezing process involving supercooled liquid particles appears to be quite well understood (Koop et al, 2000;Möhler et al, 2003;Haag et al, 2003b;Abbatt et al, 2006), uncertainties remain concerning the formation of crystalline organic and inorganic phases within partially soluble aerosols such as ammonium sulfate and certain organics, in particular oxalic acid (Zuberi et al, 2001;Abbatt et al, 2006;Zobrist et al, 2006;Shilling et al, 2006;Beaver et al, 2006). In several cases, ice formation in mixedphase particles is observed to compete with deliquescence of crystalline solids at low supersaturations (S i − 1<0.4−0.5).…”
Section: Ice Formation By Dust and Mixed-phase Particlesmentioning
confidence: 99%
“…Aerosol particles that contribute such surfaces and undergo heterogeneous freezing are termed ice nuclei (IN) (Pruppacher and Klett, 1997); the nature of IN is very diverse and not well understood. They can be composed of mineral dust (DeMott et al, 2003b;Sassen et al, 2003), sulfates (Abbatt et al, 2006), crustal material (Zuberi et al, 2002;Hung et al, 2003), carbonaceous material (Beaver et al, 2006;Cozic et al, 2006;Zobrist et al, 2006), metallic particles (Al, Fe, Ti, Cr, Zn, and Ca) DeMott et al, 2003a), and biological particles (e.g. Möhler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%